UPAYA MENINGKATKAN KEMAMPUAN BERPIKIR BERPIKIR KRITIS PESERTA DIDIK MELALUI MEDIA PEMBELAJARAN MONOPOLI KELAS V SDN KEDURUS III/430 - Bakri, Faujiah; Hendratno; Mahallisa Dyah Pristanti; Puji Astuti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to determine the critical thinking skills of students through the application of Monopoly learning media, this study was conducted for two learning cycles. Monopoly games can be used as media used by teachers in the teaching and learning process. Monopoly is an ancient game that has been developed throughout the world and then recreated into a learning medium. Through the use of monopoly learning media in class V D SDN Kedurus III / 430 Surabaya City, it can be seen that there has been an increase in the critical thinking skills of students in the learning process. This can be seen from the increase in critical thinking skills in cycle I, namely an increase in the percentage of 40.74% of 27 students who have obtained scores above learning achievement. Based on these data, it can be concluded that in cycle I, class V D students are classified in the